Outcome of emergency cerclage for advanced cervical dilatation: a retrospective analysis - Balasubramaniam, Devi; Chitra, T. V.; Panicker, Seetha (International Journal of Research in Medical Sciences, 2017)
Background: The objective was to evaluate the outcome of late second trimester emergency cerclage in patients with advanced cervical dilatation with bulging membranes. Methods: Setting: department of obstetrics and gynaecology, PSG Institute of medical sciences & research, Coimbatore, Tamil Nadu, India. This is a retrospective study of case files of patients who underwent emergency late second trimester cerclage for advanced cervical dilatation with bulging membranes between January 2009 to January 2014. McDonald’s technique was used in all the cases. Results:Altogether, 7 patients (100%) underwent late second trimester emergency cerclage between 20-28 weeks of gestational age, out of which three patients (42.86%) had term deliveries (>37w), and 3 patients (42.86 %) carried on their pregnancies to more than 32 weeks resulting in healthy live born babies. Two of them delivered by normal vaginal delivery, 4 underwent LSCS, and one patient had severe abdominal pain with bleeding and draining per vaginum after 3 days of cerclage, in view of which the stitch was removed. Subsequently, the patient expelled a live foetus weighing 620gms, which died in the Neonatal Intensive Care Unit (NICU) after 3 hours. This procedure prolonged the duration of pregnancy in all patients with a mean duration of 70.4 days. The mean gestational age at the time of delivery was 34.33 weeks. The mean birth weight was 2.18 kg and ranged between 1.97 to 2.64 kg. The mean APGAR at one minute was 8/10 and the mean duration of stay in NICU was 1.66 days. All the new-born babies were healthy at the time of discharge. The live birth rate following emergency late second trimester cerclage in this series was 85.75%. Conclusion:Favourable neonatal outcome can be accomplished in patients with cervical incompetence in the second trimester of pregnancy following emergency cervical suturing, even if performed when the membranes are bulging through the cervix.